Peran Komunitas Save Street Child Surabaya dalam Membangun Konsep Diri pada Anak Jalanan di Kota Surabaya - Novreza Malafitri; Sonya Gringsing Riadi; Saifuddin Zuhri (Jurnal Penelitian Administrasi Publik, 2020)
The phenomenon of street children has actually been developing for a long time, but now it is increasingly becoming a concern along with the increasing number of street children in various big cities. This study aims to determine the role of the Save Street Child Surabaya community in developing self-concept in street children in the city of Surabaya. This study uses a qualitative approach, how to collect data in research using interviews and observation. The results in this study are the Save Street Child Surabaya community has a large and important role in building self-concept for street children, especially in the Paliatif Park area, Ambengan Batu. Various methods are carried out such as through mentoring, approaches, making themselves like their families, and providing motivation to street children to build positive self-concepts in street children. Keywords: community role, self-concept, street children